Household health expenditure does not improve people’s subjective well-being in China - Wang, Weiwei; Sun, Yan; Li, Gen; Tang, Yingde (Frontiers in Public Health, 2024)
Household health expenditure plays a crucial role in the daily spending of individuals. Meanwhile, the attention of the public to subjective well-being (SWB) is constantly increasing in China. Household health expenditure could reduce real family income, harming personal SWB. However, the aim of household health expenditure is to improve the physical condition of an individual, and improvements in individual health could enhance personal SWB. Therefore, the effect of household health expenditure on personal SWB is uncertain; hence, it is essential to assess the effects of household health expenditure on the SWB of Chinese residents. Methods: The Chinese family panel studies database from 2016 to 2020 was applied in this study. A fixed effects model was used to examine the impact of household medical and health protection expenses on personal SWB. Fixed effects instrumental variable regression and propensity score matching were then used to conduct robustness testing. Results: On the basis of a fixed effects model, it was found that household medical and health protection expenditure did not improve the happiness and life satisfaction of individuals; rather, household health protection expenditure could significantly reduce personal happiness. Fixed effects instrumental variable regression and propensity score matching analysis supported these results. Household health protection expenditure had a greater negative impact on the happiness and life satisfaction of females compared with males. Conclusion: Household health expenditure does not improve the SWB of individuals in China; this has certain significance for the formulation of relevant policies.